Validity and reliability of the 2nd European Portuguese version of the “Consensus Auditory-Perceptual Evaluation of Voice” (II EP CAPE-V) - Almeida, Sancha C.de (2017)
A thesis submitted in partial fulfillment of the requirement for the degree of Master in Science at the Health Science School of Polytechnic Institute of Setúbal